The Significance of Food and Drink Terms in Al-Kafi a book of Al-Kulayni (died 329AH) - هادي ندى عبد الأمير (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The individual needs food and drink continuously for the continuity of life .The Holy Prophet (may God bless him and his family) and the immaculate Imams (peace be upon them) had mentioned terms of food and drink with their real and marginal meanings through (al-Kafi)،a book of al-Kulayni (died 329 AH).So، their words (peace be upon them) included several axes، including; general morals that must be adhered to، also an explanation of the ornament of what enters human body from its sanctity and so on. Also، the benefits of food and drink for the human body and its use as medicine. It is considered as a significant study that deals with the life of the individual and society and what is related to them as well. In addition to paying attention to our Arab heritage and what the immaculate imams (peace be upon them) had left us of a linguistic legacy، that is less than equal، for they are people of eloquence and rhetoric. The research revealed their linguistic and artistic aspects، (peace be upon them) and their style and skill in weaving speech، which enriches the lexical material for their use of those terms and their semantic context contained in it. The research came on two main axes، each axis included a main term، from which the rest of the terms belonging to it branched out according to their lexical field that revealed other indications of what the imams (peace be upon them) were unique to others in the linguistic use in defining the contextual path of those words.